2006
DOI: 10.1189/jlb.0705392
|View full text |Cite
|
Sign up to set email alerts
|

H2 complex controls CD4/CD8 ratio, recurrent responsiveness to repeated stimulations, and resistance to activation-induced apoptosis during T cell response to mycobacterial antigens

Abstract: Genetic variation in the major histocompatibility complex (MHC) influences susceptibility and immune responses to Mycobacterium tuberculosis in mice and humans, but connections among the severity of tuberculosis (TB), dynamic changes in T cell responses to mycobacteria, and MHC genetic polymorphisms are poorly characterized. The overall effect of the MHC genes on TB susceptibility and cellular responses to mycobacteria is moderate; thus, such studies provide reliable results only if congenic mouse strains bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Another study has demonstrated that the CD4+/CD8+ ratio was higher in susceptible TB mice [34]. In the present study, we showed that the CD4+/CD8+ ratio of T lymphocytes changes in patients without active TB infection.…”
Section: Discussionsupporting
confidence: 66%
“…Another study has demonstrated that the CD4+/CD8+ ratio was higher in susceptible TB mice [34]. In the present study, we showed that the CD4+/CD8+ ratio of T lymphocytes changes in patients without active TB infection.…”
Section: Discussionsupporting
confidence: 66%
“…H-2 genes control multiple aspects of the anti- M.tb immune response, including the generation of antibodies [12], survival of mycobacterial antigen-specific T cells in vitro [13, 14], and in vitro IFN-γ levels produced by T cells [16]. Here, we focused our analysis to identify H-2 k -dependent (comparison of C57BL/6 and C57BL/6 H-2 k data) and -independent (comparison of C57BL/6 H-2 k , CBA/J, C3H/HeJ data) contributions to the anti- M.tb immune response during early M.tb infection in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence that polymorphisms in the MHC region in both species have modest effects on TB susceptibility (reviewed in refs. 22,59), and profound effects on the immune response to mycobacterial antigens 73–75 . However, the number of polymorphic genes located within the MHC region and potentially involved in the anti‐mycobacterial immune response is very large, even if classical Class I and Class II antigen‐presenting molecules and TNF‐like products are left aside.…”
Section: Complex Cases For Interspecies Comparisons: Allelic Variantsmentioning
confidence: 99%